T Helper Cell Lineage-Defining Transcription Factors: Potent Targets for Specific GVHD Therapy? - Campe, Julia; Ullrich, Evelyn (Frontiers in Immunology, 2022)
Allogenic hematopoietic stem cell transplantation (allo-HSCT) represents a potent and potentially curative treatment for many hematopoietic malignancies and hematologic disorders in adults and children. Its success is based on a complete replacement of the patients’ immune system by a myeloablative conditioning regimen and reconstitution from a healthy donor stem cell graft. The donor-derived immunity can prevent disease relapse but is also responsible for the induction of graft-versus-host disease (GVHD) as one of the main and potentially life-threatening complications of allo-HSCT. The pathophysiology of acute GVHD is not yet completely understood. In general, acute GVHD is driven by the inflammatory and cytotoxic effect of alloreactive donor T cells. Since several experimental approaches indicate that CD4 T cells play an important role in initiation and progression of acute GVHD, the contribution of the different CD4 T helper (Th) cell subtypes in the pathomechanism and regulation of the disease are a central point of current research. Th lineages derive from naïve CD4 T cell progenitors and lineage commitment is initiated by the surrounding cytokine milieu and subsequent changes in the transcription factor (TF) profile. Each T cell subtype has its own effector characteristics, immunologic function, and lineage specific cytokine profile, leading to the association with different immune responses and diseases. Acute GVHD is thought to be mainly driven by the Th1/Th17 axis, whereas Treg cells are attributed to attenuate GVHD effects. As the differentiation of each Th subset highly depends on the specific composition of activating and repressing TFs, these present a potent target to alter the Th cell landscape towards a GVHD-ameliorating direction, e.g. by inhibiting Th1 and Th17 differentiation. The finding, that targeting of Th1 and Th17 differentiation appears more effective for GVHD-prevention than a strategy to inhibit Th1 and Th17 cytokines supports this concept. In this review, we shed light on the current advances of potent TF inhibitors to alter Th cell differentiation and consecutively attenuate GVHD. We focus especially on preclinical studies and outcomes of TF inhibition in murine GVHD models. Finally, we point out the possible impact of a Th cell subset-specific immune modulation in context of GVHD.